Comparative Analysis of Operational and Liquidity Risks of Islamic Banks in the ASEAN Region Using Basel III - Wahyudi, Bintang Tri; Zuliansyah, A.; Musthofa, Ujang Hanief (Indonesian Journal of Islamic Economics and Finance, 2024)
This research aims to analyze the differences in operational and liquidity risks of Islamic banks in the ASEAN region based on the Basel III framework. The study employs a quantitative methodology, utilizing the Kruskal-Wallis analysis and Mann-Whitney U test, drawing on financial reports from Islamic banks from 2021 to 2023. Key indicators examined include the Operational Risk Capital Charge (ORCC), Net Stable Funding Ratio (NSFR), and Liquidity Coverage Ratio (LCR). The findings reveal significant differences in the management of operational risk (ORCC) and long-term funding stability (NSFR), while no significant differences were observed in short-term liquidity (LCR). It was noted that predominantly Muslim countries are better equipped to handle operational risks, whereas banks in smaller markets face liquidity challenges. However, the study is limited to Islamic banks in five ASEAN countries and does not consider external variables such as macroeconomic conditions. Overall, these findings contribute to the existing literature on risk management in Islamic banks within the ASEAN region and offer valuable insights for regulators to develop policies tailored to local characteristics.